A precursor for improving the properties of refractory materials for cement rotary kiln and its application
By adding magnesium-based lanthanum hexaphthalate precursor to the square magnesium-magnesium aluminum spinel refractory material for cement rotary kilns, the problems of low material strength and poor resistance to alkaline media are solved, and the high strength, good thermal shock stability and strong resistance to alkaline media corrosion are achieved.
Patent Information
- Application Number
- CN202411057265.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-02
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-08-02
AI Technical Summary
The existing square magnesium-magnesium-aluminum spinel refractory materials for cement rotary kilns have problems of low strength and poor resistance to alkaline media, and it is difficult to simultaneously improve the strength, thermal shock stability and resistance to alkaline media.
By adding magnesium-based lanthanum hexaluminate precursor to the refractory material, magnesium-based lanthanum hexaluminate precursor is synthesized by low-temperature solid phase method, and added to the square magnesium-magnesium-aluminum spinel refractory material for cement rotary kilns, the strength, thermal shock stability and resistance to alkaline media corrosion are improved.
The compressive strength, thermal shock stability and alkaline media corrosion resistance of square magnesium-magnesium aluminum spinel refractory materials for cement rotary kilns have been significantly improved, ensuring the stability and service life of the material in high temperature and alkaline media environments.
Smart Images

Figure CN118619655B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of refractory materials for cement rotary kilns, and specifically relates to a precursor for improving the properties of refractory materials for cement rotary kilns and its application. Background Art
[0002] The research and development of chromium-free alkaline refractory materials for cement rotary kilns is one of the hot topics in national environmental protection work.
[0003] Periclite-magnesium-aluminum-spinel refractory material maintains good stability in oxidizing or reducing atmospheres and is one of the main varieties to replace magnesium-chrome refractory materials for cement rotary kilns. However, there are a certain amount of impurities in traditional periclase-magnesium-aluminum-spinel refractory materials, which makes the material strength low and has poor resistance to alkaline medium erosion, which seriously affects its service life.
[0004] For example, the patented technology of "Lightweight periclase-magnesium-aluminum spinel refractory material for cement rotary kiln and preparation method thereof" (CN103864434A) prepares periclase-magnesium-aluminum spinel refractory material for cement rotary kiln by adding porous periclase-magnesium-aluminum spinel ceramic raw materials. Although it is beneficial to reduce the thermal conductivity of refractory materials and play a role in saving energy, the prepared refractory materials have low strength and poor corrosion resistance due to the presence of a large number of holes and gaps inside.
[0005] For example, the patented technology of "chrome-free refractory with excellent kiln lining adhesion for cement rotary kiln" (CN105314992A) uses only periclase and magnesia-alumina spinel as the main raw materials to prepare chrome-free refractory for cement rotary kiln. Although the preparation process is convenient, it saves raw materials and reduces costs, but the impurity content is relatively high, which affects the strength, thermal shock stability and medium erosion resistance of the refractory.
[0006] For example, the patented technology of "a periclase-composite spinel brick for cement rotary kiln firing zone and its preparation method" (CN106927837A) adds zinc-aluminum spinel to the periclase-magnesium-aluminum spinel refractory material for cement rotary kiln. Although it is beneficial to improve the refractory material's resistance to alkaline medium erosion, zinc-aluminum spinel has no obvious effect on the kiln skin performance of the refractory material, and at the same time introduces a variety of impurities, reducing the strength of the material.
[0007] For example, the patented technology of "periclite-calcium-containing spinel bricks for cement rotary kiln firing zone and preparation method thereof" (CN103467121A) prepares calcium-containing spinel and adds it to the periclase-magnesium-aluminum spinel refractory material. Although calcium-containing spinel is beneficial to improve the alkaline medium erosion resistance of periclase-magnesium-aluminum spinel for cement rotary kiln, calcium-containing spinel increases the content of low melting point phase in the refractory material, which significantly reduces its strength and thermal shock stability.
[0008] For example, the patented technology of "A magnesia-alumina spinel anti-scaling shaped refractory material for cement kiln and its preparation method and application" (CN102391002A) prepares cordierite-magnesia-alumina spinel refractory material for cement rotary kiln by adding a series of additives such as silica sol, silicon nitride, organic binder and high-efficiency water reducer. Although it is beneficial to improve the anti-scaling ability of refractory materials, the addition of a large number of additives leads to complex processes and increased costs.
[0009] In summary, the existing methods can improve the performance of refractory materials from different angles, but either reduce the thermal conductivity, but reduce the strength and have poor erosion resistance, or improve the erosion resistance, but reduce the strength, etc. These methods cannot meet the requirements of simultaneously improving the performance of cement rotary kiln refractory materials.
[0010] Therefore, it is necessary to develop a material that can improve the strength, thermal shock stability and resistance to alkaline medium erosion of refractory materials.
[0011] The inventors considered adding magnesium-based lanthanum hexaaluminate to the refractory material. The latter has excellent properties such as low thermal conductivity, high thermal expansion coefficient, good thermal stability, thermal insulation and optical properties, and is widely used in many fields such as military, solid lasers and thermal barrier coating ceramics. However, it is rarely used in refractory materials.
[0012] There are many methods for preparing magnesium-based lanthanum hexaaluminate. For example, CN1730210A provides a method for preparing magnesium-based lanthanum hexaaluminate powder by coprecipitation. CN106518046A provides a method for preparing magnesium-based lanthanum hexaaluminate powder by co-ion complexation. There is a report "A method for preparing magnesium-based lanthanum hexaaluminate spherical spray powder" (CN109160811A) using lanthanum oxide, magnesium oxide and aluminum oxide nanopowders as raw materials, anhydrous ethanol as solvent, mixing and drying, and synthesizing single-phase magnesium-based lanthanum hexaaluminate by high-temperature solid-phase reaction.
[0013] The above methods may require expensive nano-raw materials and relatively high synthesis temperatures (1350-1700° C.) to synthesize magnesium-based lanthanum hexaaluminate, or the prepared powder may have irregular morphology and poor dispersibility.
[0014] Therefore, the inventors improved the magnesium-based lanthanum hexaaluminate, synthesized the magnesium-based lanthanum hexaaluminate precursor by low-temperature solid-phase method, and then added it to the periclase-magnesium-aluminum spinel refractory material for cement rotary kiln to improve the refractory material strength, thermal shock stability and resistance to alkaline medium erosion. Summary of the invention
[0015] In order to provide a material that can improve the properties of refractory materials for cement rotary kilns, the inventor provides a precursor that can improve the strength, thermal shock stability and alkaline medium corrosion resistance of refractory materials for cement rotary kilns.
[0016] The invention provides a precursor for improving the properties of refractory materials for cement rotary kilns. The raw materials of the precursor contain the following substances in the following amounts: 1 part of magnesium nitrate hexahydrate, 1 part of lanthanum nitrate hexahydrate, 11 parts of aluminum nitrate nonahydrate, and 10-17 parts of citric acid monohydrate.
[0017] Preferably, the precursor raw material contains the following materials in the following amounts: 1 part of magnesium nitrate hexahydrate, 1 part of lanthanum nitrate hexahydrate, 11 parts of aluminum nitrate nonahydrate, and 12-16 parts of citric acid monohydrate.
[0018] Optimally, the precursor raw material contains the following amounts of materials: 1 part of magnesium nitrate hexahydrate, 1 part of lanthanum nitrate hexahydrate, 11 parts of aluminum nitrate nonahydrate, and 14 parts of citric acid monohydrate.
[0019] The present invention also provides a method for preparing the above-mentioned precursor, which comprises the following steps: weighing various materials according to a ratio, mixing, grinding at room temperature for 40-90 minutes, drying at 100-150° C. for 8-15 hours, and then heat treating at 1000-1200° C. for 2-5 hours to obtain a precursor.
[0020] The precursor prepared by the present invention has obvious flake structural characteristics, can effectively play a bridging role in the material system, and improve the strength, thermal shock stability and alkaline medium corrosion resistance of the refractory material.
[0021] The second object of the present invention is to provide a periclase-magnesia-alumina spinel refractory material for cement rotary kiln, the raw materials of which contain the following materials in parts by weight: 60 parts of aggregate, 30-50 parts of powder, 1-5 parts of precursor and 5-10 parts of adhesive.
[0022] Preferably, the raw material of the refractory material contains the following materials in parts by weight: 60 parts of aggregate, 35-45 parts of powder, 3-4 parts of the precursor described in the above scheme and 5-10 parts of binder.
[0023] In the refractory material:
[0024] The particle size of the precursor is less than 0.1 mm, and the precursor needs to be crushed and passed through a 0.1 mm sieve.
[0025] The 60 parts of aggregate contain the following materials in parts by weight: 10-20 parts of fused magnesia aggregate with a particle size of 3-5 mm, 20-40 parts of fused magnesia aggregate with a particle size of 1-3 mm, and 10-20 parts of fused magnesia aggregate with a particle size of 0.088-1 mm;
[0026] Preferably, 60 parts of aggregate contain the following materials in parts by weight: 12-18 parts of fused magnesia aggregate with a particle size of 3-5 mm, 25-35 parts of fused magnesia aggregate with a particle size of 1-3 mm, and 12-18 parts of fused magnesia aggregate with a particle size of 0.088-1 mm;
[0027] Preferably, 60 parts of aggregate contain the following materials by weight: 15 parts of fused magnesia aggregate with a particle size of 3-5 mm, 30 parts of fused magnesia aggregate with a particle size of 1-3 mm, and 15 parts of fused magnesia aggregate with a particle size of 0.088-1 mm.
[0028] The 30-50 parts of powder contain the following materials by weight: 20-30 parts of fused magnesia powder and 10-20 parts of active spinel powder;
[0029] Preferably, the 30-50 parts of powder contain the following materials in parts by weight: 25 parts of fused magnesia powder and 12-18 parts of active spinel powder.
[0030] The purity of the magnesium nitrate hexahydrate is ≥99.9%; and the particle size of the magnesium nitrate hexahydrate is ≤5 μm.
[0031] The purity of the lanthanum nitrate hexahydrate is ≥99.9%; and the particle size of the lanthanum nitrate hexahydrate is ≤5 μm.
[0032] The purity of the aluminum nitrate nonahydrate is ≥99.9%; the particle size of the aluminum nitrate nonahydrate is ≤5 μm.
[0033] The purity of the citric acid monohydrate is ≥99.9%; and the particle size of the citric acid monohydrate is ≤5 μm.
[0034] The chemical composition of the fused magnesia aggregate is: MgO=96.5-97.5wt%, Al2O3≤0.3wt%, CaO≤0.7wt%, SiO2≤0.9wt%, Fe2O3≤0.5wt%.
[0035] The particle size of the fused magnesia powder is less than 0.1 mm; the chemical composition of the fused magnesia powder is: MgO=96.5-97.5wt%, Al2O3≤0.3wt%, CaO≤0.7wt%, SiO2≤0.9wt%, Fe2O3≤0.5wt%.
[0036] The particle size of the active spinel powder is less than 0.1 mm; the chemical composition of the active spinel powder is: MgO=34.5-36.5wt%, Al2O3=63.5-65.5wt%, CaO≤0.7wt%, SiO2≤0.9wt%, Fe2O3≤0.5wt%.
[0037] The adhesive is a polyvinyl alcohol aqueous solution with a concentration of 10%.
[0038] The third object of the present invention is to provide a method for preparing a periclase-magnesia-alumina spinel refractory material for a cement rotary kiln, the method comprising the following steps:
[0039] Step 1: Weigh each ingredient according to the ratio and set aside;
[0040] Step 2: Using anhydrous ethanol as solvent, wet-mix the fused magnesia powder, active spinel powder and precursor powder for 3-8 hours, and then dry at 90-130° C. for 12-36 hours, and grind to a particle size of less than 0.1 mm to obtain a mixed powder;
[0041] Step 3, placing the fused magnesia aggregate with a particle size of 3-5mm, the fused magnesia aggregate with a particle size of 1-3mm, the fused magnesia aggregate with a particle size of 0.088-1mm and the mixed powder in step 2 in a mixing mill and mixing for 30 minutes to obtain a mixed refractory mud;
[0042] Step 4: Mix the refractory material mud and the binder after mixing and grinding in step 3, put the mixture into a mold, seal it, move it to the pressure cabin of the isostatic press, and perform cold isostatic pressing to obtain a refractory embryo body;
[0043] The specific operation of the cold isostatic pressing is: first, the pressure is increased to 50MPa at a rate of 4MPa / s, increased to 80MPa at a rate of 5MPa / s, increased to 110MPa at a rate of 10MPa / s, increased to 140MPa at a rate of 6MPa / s, increased to 200MPa at a rate of 8MPa / s, and maintained for 5min; then, the pressure is reduced to 140MPa at a rate of 5MPa / s, reduced to 110MPa at a rate of 6MPa / s, reduced to 80MPa at a rate of 8MPa / s, reduced to 50MPa at a rate of 5MPa / s, and reduced to 2MPa at a rate of 5MPa / s; finally, the pressure is unloaded to normal pressure;
[0044] Step 5: Dry the refractory material body at 100-120° C. for 12-36 hours, and calcine at 1600-1800° C. for 3-5 hours to obtain the periclase-magnesia-alumina spinel refractory material for cement rotary kiln.
[0045] The concentration of the polyvinyl alcohol aqueous solution is 10%.
[0046] Due to the adoption of the above technical solution, the present invention has the following positive effects compared with the prior art:
[0047] 1. The precursor powder synthesized in the present invention is magnesium-based lanthanum hexaaluminate, which has a unique lamellar structure, uniform grain size, good dispersibility in refractory materials, and is easy to prepare and control.
[0048] 2. Based on the characteristics of the magnesium-based lanthanum hexaaluminate precursor powder, the addition of the magnesium-based lanthanum hexaaluminate precursor powder to the refractory material for the cement rotary kiln in the present invention can improve the strength and thermal shock stability of the periclase-magnesium aluminate spinel refractory material for the cement rotary kiln.
[0049] 3. The magnesium-based lanthanum hexaaluminate precursor powder added in the present invention is a high-melting-point rare earth additive and can effectively resist erosion by alkaline media.
[0050] 4. The active spinel powder used in the present invention has good sintering activity, and can effectively improve the sintering activity of periclase-magnesia-alumina spinel refractory materials for cement rotary kilns, thereby improving the strength of the materials.
[0051] 5. The present invention uses periclase, active spinel, magnesium-based lanthanum hexaaluminate and polyvinyl alcohol as main raw materials, and forms them through a cold isostatic pressing process, so that the performance of the prepared refractory material is more controllable.
[0052] 6. The periclase-magnesium-aluminum spinel refractory material for cement rotary kiln prepared by the present invention has been tested: the compressive strength is 85-110MPa; the residual flexural strength retention rate is not less than 75% after 1100℃ thermal shock 3 times and air cooling; no obvious erosion and penetration are found in the alkaline medium erosion resistance test.
[0053] Therefore, the refractory material provided by the present invention has low equipment requirements and simple process, and the prepared periclase-magnesium-aluminum spinel refractory material for cement rotary kiln has the advantages of high strength, good thermal shock stability and strong resistance to alkaline medium corrosion. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 : Scanning electron microscope (SEM) images of Examples 1-3 and Comparative Examples 1 and 2;
[0055] Figure 2 : Example 4, Comparative Example 3 longitudinal section appearance of the sample after anti-alkaline medium erosion, the left picture is Comparative Example 3, and the right picture is Example 4;
[0056] Figure 3 It is a process flow chart of Example 1 and Example 4 of the present invention. DETAILED DESCRIPTION
[0057] The present invention is further described below in conjunction with specific embodiments, but is not intended to limit the scope of protection thereof:
[0058] In this specific implementation mode:
[0059] The purity of the magnesium nitrate hexahydrate is ≥99.9%; and the particle size of the magnesium nitrate hexahydrate is ≤5 μm.
[0060] The purity of the lanthanum nitrate hexahydrate is ≥99.9%; and the particle size of the lanthanum nitrate hexahydrate is ≤5 μm.
[0061] The purity of the aluminum nitrate nonahydrate is ≥99.9%; the particle size of the aluminum nitrate nonahydrate is ≤5 μm.
[0062] The purity of the citric acid monohydrate is ≥99.9%; and the particle size of the citric acid monohydrate is ≤5 μm.
[0063] The chemical composition of the fused magnesia aggregate is: MgO=96.5-97.5wt%, Al2O3≤0.3wt%, CaO≤0.7wt%, SiO2≤0.9wt%, Fe2O3≤0.5wt%.
[0064] The particle size of the fused magnesia powder is less than 0.1 mm; the chemical composition of the fused magnesia powder is: MgO=96.5-97.5wt%, Al2O3≤0.3wt%, CaO≤0.7wt%, SiO2≤0.9wt%, Fe2O3≤0.5wt%.
[0065] The particle size of the active spinel powder is less than 0.1 mm; the chemical composition of the active spinel powder is: MgO=34.5-36.5wt%, Al2O3=63.5-65.5wt%, CaO≤0.7wt%, SiO2≤0.9wt%, Fe2O3≤0.5wt%.
[0066] The concentration of the polyvinyl alcohol aqueous solution is 10%. The preparation method of the solution is to dissolve 10g of polyvinyl alcohol in 90g of water and stir evenly to obtain the solution.
[0067] Example 1: Magnesium-based lanthanum hexaaluminate precursor
[0068] 1. Raw materials: The raw materials of the magnesium-based lanthanum hexaaluminate precursor powder are: magnesium nitrate hexahydrate: lanthanum nitrate hexahydrate: aluminum nitrate nonahydrate: citric acid monohydrate, the molar ratio of which is 1:1:11:12 (25.6 g magnesium nitrate hexahydrate, 43.3 g lanthanum nitrate hexahydrate, 412.5 g aluminum nitrate nonahydrate, 252 g citric acid monohydrate after conversion)
[0069] 2. Preparation method
[0070] The ingredients are prepared in a material ratio of magnesium nitrate hexahydrate: lanthanum nitrate hexahydrate: aluminum nitrate nonahydrate: citric acid monohydrate of 1:1:11:12, mixed, ground at room temperature for 60 minutes, dried at 110°C for 12 hours, and then heat treated at 1000°C for 3 hours to obtain a magnesium-based lanthanum hexaaluminate precursor.
[0071] Example 2: Magnesium-based lanthanum hexaaluminate precursor
[0072] 1. Raw materials: The raw materials of the magnesium-based lanthanum hexaaluminate precursor powder are magnesium nitrate hexahydrate: lanthanum nitrate hexahydrate: aluminum nitrate nonahydrate: citric acid monohydrate in a ratio of 1:1:11:14 (25.6 g magnesium nitrate hexahydrate, 43.3 g lanthanum nitrate hexahydrate, 412.5 g aluminum nitrate nonahydrate, 294 g citric acid monohydrate)
[0073] 2. Preparation method
[0074] The ingredients are prepared in a material ratio of magnesium nitrate hexahydrate: lanthanum nitrate hexahydrate: aluminum nitrate nonahydrate: citric acid monohydrate of 1:1:11:14, mixed, ground at room temperature for 60 minutes, dried at 110°C for 12 hours, and then heat treated at 1000°C for 3 hours to obtain a magnesium-based lanthanum hexaaluminate precursor.
[0075] Example 3: Magnesium-based lanthanum hexaaluminate precursor
[0076] 1. Raw materials: The raw materials of the magnesium-based lanthanum hexaaluminate precursor powder are magnesium nitrate hexahydrate: lanthanum nitrate hexahydrate: aluminum nitrate nonahydrate: citric acid monohydrate in a ratio of 1:1:11:16 (25.6 g magnesium nitrate hexahydrate, 43.3 g lanthanum nitrate hexahydrate, 412.5 g aluminum nitrate nonahydrate, 336 g citric acid monohydrate)
[0077] 2. Preparation method
[0078] The ingredients are prepared in a material ratio of magnesium nitrate hexahydrate: lanthanum nitrate hexahydrate: aluminum nitrate nonahydrate: citric acid monohydrate of 1:1:11:16, mixed, ground at room temperature for 60 minutes, dried at 110°C for 12 hours, and then heat treated at 1000°C for 3 hours to obtain a magnesium-based lanthanum hexaaluminate precursor.
[0079] Comparative Example 1: Magnesium-based lanthanum hexaaluminate precursor
[0080] Same as Example 1, except that citric acid monohydrate was not added, specifically:
[0081] 1. Raw materials: The raw materials of the magnesium-based lanthanum hexaaluminate precursor powder are magnesium nitrate hexahydrate: lanthanum nitrate hexahydrate: aluminum nitrate nonahydrate in a ratio of 1:1:11 (25.6 g magnesium nitrate hexahydrate, 43.3 g lanthanum nitrate hexahydrate, 412.5 g aluminum nitrate nonahydrate)
[0082] 2. Preparation method
[0083] The materials are prepared in a material ratio of magnesium nitrate hexahydrate: lanthanum nitrate hexahydrate: aluminum nitrate nonahydrate of 1:1:11, mixed, ground at room temperature for 60 minutes, dried at 110°C for 12 hours, and then heat treated at 1000°C for 3 hours to obtain a magnesium-based lanthanum hexaaluminate precursor.
[0084] Comparative Example 2: Magnesium-based lanthanum hexaaluminate precursor
[0085] Same as Example 1, except that the preparation method is different, specifically:
[0086] 1. Raw materials: The raw materials of the magnesium-based lanthanum hexaaluminate precursor powder are magnesium nitrate: lanthanum nitrate: aluminum nitrate: citric acid in a ratio of 1:1:11:14 (32.5 g lanthanum nitrate, 14.8 g magnesium nitrate, 233.2 g aluminum nitrate, 268.8 g citric acid)
[0087] 2. Preparation method
[0088] 32.5 g of lanthanum nitrate, 14.8 g of magnesium nitrate and 233.2 g of aluminum nitrate were added to 1500 mL of water, stirred evenly, and then 268.8 g of citric acid was added and mixed. The mixture was heated to 90° C., stirred for 5 h and then filtered. The obtained solid was dried at 200° C. for 8 h to obtain a precursor.
[0089] Experimental Example 1: Microscopic observation of the precursor
[0090] 1. Samples: Examples 1, 2, 3, and Comparative Examples 1 and 2.
[0091] 2. Observation method: The precursor sample was crushed and passed through a 0.1 mm sieve, and then the prepared magnesium-based lanthanum hexaaluminate precursor powder was observed by microscopic morphology using a scanning electron microscope (SEM).
[0092] 3. Experimental results: see Figure 1 .
[0093] The results show that the grains of Examples 1-3 provided by the present invention are uniform in size and have obvious flaky structural characteristics, among which Example 2 has the best effect, and the grain size of the magnesium-based lanthanum hexaaluminate phase is uniform and the flaky structural characteristics are the most obvious.
[0094] The magnesium-based lanthanum hexaaluminate provided by the invention has obvious flaky structural characteristics, and the structure can play a role of cross-linking in refractory materials, thereby improving the strength, thermal shock stability and alkaline medium corrosion resistance of the refractory materials.
[0095] Example 4: A periclase-magnesia-alumina spinel refractory material for cement rotary kiln
[0096] 1. Raw materials:
[0097] 25 kg of fused magnesia powder (particle size less than 0.1 mm), 15 kg of active spinel powder (particle size less than 0.1 mm), 1 kg of magnesium-based lanthanum hexaaluminate precursor (prepared in Example 2), 15 kg of fused magnesia aggregate with a particle size of 3-5 mm, 30 kg of fused magnesia aggregate with a particle size of 1-3 mm, 15 kg of fused magnesia aggregate with a particle size of 0.088-1 mm, and 5 kg of polyvinyl alcohol aqueous solution (concentration of 10%).
[0098] Anhydrous ethanol was also used as solvent in the preparation process.
[0099] 2. The preparation steps are:
[0100] Step 1: crush the precursor, pass it through a 0.1 mm sieve to obtain precursor powder, weigh each component according to the raw material, and set aside;
[0101] Step 2: fused magnesia powder, active spinel powder and magnesium-based lanthanum hexaaluminate precursor powder (prepared in Example 2) are wet mixed for 6 hours with anhydrous ethanol as solvent, and then dried at 110° C. for 24 hours, and ground to a particle size of less than 0.1 mm to obtain a mixed powder;
[0102] Step 3, placing the fused magnesia aggregate with a particle size of 3-5mm, the fused magnesia aggregate with a particle size of 1-3mm, the fused magnesia aggregate with a particle size of 0.088-1mm and the mixed powder in a mixing mill and mixing for 30 minutes to obtain a refractory mud after mixing and grinding;
[0103] Step 4: Mix the mixed refractory mud and the polyvinyl alcohol aqueous solution, place the mixture in a mold, seal it, and move it to the pressure cabin of the isostatic press. First, increase the pressure to 50MPa at a rate of 4MPa / s, increase the pressure to 80MPa at a rate of 5MPa / s, increase the pressure to 110MPa at a rate of 10MPa / s, increase the pressure to 140MPa at a rate of 6MPa / s, and increase the pressure to 200MPa at a rate of 8MPa / s, and maintain the pressure for 5min; then reduce the pressure to 140MPa at a rate of 5MPa / s, reduce the pressure to 110MPa at a rate of 6MPa / s, reduce the pressure to 80MPa at a rate of 8MPa / s, reduce the pressure to 50MPa at a rate of 5MPa / s, and reduce the pressure to 2MPa at a rate of 5MPa / s; finally unload it to normal pressure; perform cold isostatic pressing to obtain a refractory embryo;
[0104] Step 5: Dry the refractory body at 110° C. for 24 hours, and calcine at 1600° C. for 3 hours to obtain the periclase-magnesia-alumina spinel refractory for cement rotary kiln.
[0105] The process flow chart of Example 1 and Example 4 of the present invention is shown in Figure 3 .
[0106] Example 5: A periclase-magnesia-alumina spinel refractory material for cement rotary kiln
[0107] 1. The raw materials are the same as those in Example 4, except that 2 kg of magnesium-based lanthanum hexaaluminate precursor (prepared in Example 2) is added.
[0108] 2. The preparation steps are:
[0109] Step 1: crush the precursor, pass it through a 0.1 mm sieve to obtain precursor powder, weigh each component according to the raw material, and set aside;
[0110] Step 2: Using anhydrous ethanol as solvent, wet-mix the fused magnesia powder, active spinel powder and magnesium-based lanthanum hexaaluminate precursor powder for 6 hours, and then drying at 110° C. for 24 hours, and grinding the powder to a particle size of less than 0.1 mm to obtain a mixed powder;
[0111] Step 3, placing the fused magnesia aggregate with a particle size of 3-5mm, the fused magnesia aggregate with a particle size of 1-3mm, the fused magnesia aggregate with a particle size of 0.088-1mm and the mixed powder in step 2 in a mixing mill and mixing for 30 minutes to obtain a mixed refractory mud;
[0112] Step 4: Mix the mixed refractory mud and the polyvinyl alcohol aqueous solution, place the mixture in a mold, seal it, and move it to the pressure cabin of the isostatic press. First, increase the pressure to 50MPa at a rate of 4MPa / s, increase the pressure to 80MPa at a rate of 5MPa / s, increase the pressure to 110MPa at a rate of 10MPa / s, increase the pressure to 140MPa at a rate of 6MPa / s, and increase the pressure to 200MPa at a rate of 8MPa / s, and maintain the pressure for 5min; then reduce the pressure to 140MPa at a rate of 5MPa / s, reduce the pressure to 110MPa at a rate of 6MPa / s, reduce the pressure to 80MPa at a rate of 8MPa / s, reduce the pressure to 50MPa at a rate of 5MPa / s, and reduce the pressure to 2MPa at a rate of 5MPa / s; finally unload it to normal pressure; perform cold isostatic pressing to obtain a refractory embryo;
[0113] Step 5: Dry the refractory body at 110° C. for 24 hours, and calcine at 1600° C. for 3 hours to obtain the periclase-magnesia-alumina spinel refractory for cement rotary kiln.
[0114] Example 6: A periclase-magnesia-alumina spinel refractory material for cement rotary kiln
[0115] 1. The raw materials are the same as those in Example 4, except that 3 kg of magnesium-based lanthanum hexaaluminate precursor (prepared in Example 2) is added.
[0116] 2. The preparation steps are:
[0117] Step 1: crush the precursor, pass it through a 0.1 mm sieve to obtain precursor powder, weigh each component according to the raw material, and set aside;
[0118] Step 2: Using anhydrous ethanol as solvent, wet-mix the fused magnesia powder, active spinel powder and magnesium-based lanthanum hexaaluminate precursor powder for 6 hours, and then drying at 110° C. for 24 hours, and grinding the powder to a particle size of less than 0.1 mm to obtain a mixed powder;
[0119] Step 3, placing the fused magnesia aggregate with a particle size of 3-5mm, the fused magnesia aggregate with a particle size of 1-3mm, the fused magnesia aggregate with a particle size of 0.088-1mm and the mixed powder in step 2 in a mixing mill and mixing for 30 minutes to obtain a mixed refractory mud;
[0120] Step 4: Mix the mixed refractory mud and the polyvinyl alcohol aqueous solution, place the mixture in a mold, seal it, and move it to the pressure cabin of the isostatic press. First, increase the pressure to 50MPa at a rate of 4MPa / s, increase the pressure to 80MPa at a rate of 5MPa / s, increase the pressure to 110MPa at a rate of 10MPa / s, increase the pressure to 140MPa at a rate of 6MPa / s, and increase the pressure to 200MPa at a rate of 8MPa / s, and maintain the pressure for 5min; then reduce the pressure to 140MPa at a rate of 5MPa / s, reduce the pressure to 110MPa at a rate of 6MPa / s, reduce the pressure to 80MPa at a rate of 8MPa / s, reduce the pressure to 50MPa at a rate of 5MPa / s, and reduce the pressure to 2MPa at a rate of 5MPa / s; finally unload it to normal pressure; perform cold isostatic pressing to obtain a refractory embryo;
[0121] Step 5: Dry the refractory body at 110° C. for 24 hours, and calcine at 1600° C. for 3 hours to obtain the periclase-magnesia-alumina spinel refractory for cement rotary kiln.
[0122] Example 7: A periclase-magnesia-alumina spinel refractory material for cement rotary kiln
[0123] 1. The raw materials are the same as those in Example 4, except that 4 kg of magnesium-based lanthanum hexaaluminate precursor (prepared in Example 2) is added.
[0124] 2. The preparation steps are:
[0125] Step 1: crush the precursor, pass it through a 0.1 mm sieve to obtain precursor powder, weigh each component according to the raw material, and set aside;
[0126] Step 2: 25 wt% of fused magnesia powder, 15 wt% of active spinel powder and 4 wt% of magnesium-based lanthanum hexaaluminate precursor powder are wet mixed for 6 hours with anhydrous ethanol as solvent, and then dried at 110° C. for 24 hours, and ground to a particle size of less than 0.1 mm to obtain a mixed powder;
[0127] Step 3, placing the fused magnesia aggregate with a particle size of 3-5mm, the fused magnesia aggregate with a particle size of 1-3mm, the fused magnesia aggregate with a particle size of 0.088-1mm and the mixed powder in step 2 in a mixing mill and mixing for 30 minutes to obtain a mixed refractory mud;
[0128] Step 4: Mix the mixed refractory mud and the polyvinyl alcohol aqueous solution, place the mixture in a mold, seal it, and move it to the pressure cabin of the isostatic press. First, increase the pressure to 50MPa at a rate of 4MPa / s, increase the pressure to 80MPa at a rate of 5MPa / s, increase the pressure to 110MPa at a rate of 10MPa / s, increase the pressure to 140MPa at a rate of 6MPa / s, and increase the pressure to 200MPa at a rate of 8MPa / s, and maintain the pressure for 5min; then reduce the pressure to 140MPa at a rate of 5MPa / s, reduce the pressure to 110MPa at a rate of 6MPa / s, reduce the pressure to 80MPa at a rate of 8MPa / s, reduce the pressure to 50MPa at a rate of 5MPa / s, and reduce the pressure to 2MPa at a rate of 5MPa / s; finally unload it to normal pressure; perform cold isostatic pressing to obtain a refractory embryo;
[0129] Step 5: Dry the refractory material body at 110° C. for 24 hours, and calcine at 1800° C. for 5 hours to obtain the periclase-magnesia-alumina spinel refractory material for cement rotary kiln.
[0130] Example 8: A periclase-magnesia-alumina spinel refractory material for cement rotary kiln
[0131] 1. The raw materials are the same as those in Example 4, except that 5 kg of magnesium-based lanthanum hexaaluminate precursor (prepared in Example 2) is added.
[0132] 2. The preparation steps are:
[0133] Step 1: crush the precursor, pass it through a 0.1 mm sieve to obtain precursor powder, weigh each component according to the raw material, and set aside;
[0134] Step 2: Using anhydrous ethanol as solvent, wet-mix the fused magnesia powder, active spinel powder and magnesium-based lanthanum hexaaluminate precursor powder for 6 hours, and then drying at 110° C. for 24 hours, and grinding the powder to a particle size of less than 0.1 mm to obtain a mixed powder;
[0135] Step 3, placing the fused magnesia aggregate with a particle size of 3-5mm, the fused magnesia aggregate with a particle size of 1-3mm, the fused magnesia aggregate with a particle size of 0.088-1mm and the mixed powder in step 2 in a mixing mill and mixing for 30 minutes to obtain a mixed refractory mud;
[0136] Step 4: Mix the mixed refractory mud and the polyvinyl alcohol aqueous solution, place the mixture in a mold, seal it, and move it to the pressure cabin of the isostatic press. First, increase the pressure to 50MPa at a rate of 4MPa / s, increase the pressure to 80MPa at a rate of 5MPa / s, increase the pressure to 110MPa at a rate of 10MPa / s, increase the pressure to 140MPa at a rate of 6MPa / s, and increase the pressure to 200MPa at a rate of 8MPa / s, and maintain the pressure for 5min; then reduce the pressure to 140MPa at a rate of 5MPa / s, reduce the pressure to 110MPa at a rate of 6MPa / s, reduce the pressure to 80MPa at a rate of 8MPa / s, reduce the pressure to 50MPa at a rate of 5MPa / s, and reduce the pressure to 2MPa at a rate of 5MPa / s; finally unload it to normal pressure; perform cold isostatic pressing to obtain a refractory embryo;
[0137] Step 5: Dry the refractory material body at 110° C. for 24 hours, and calcine at 1800° C. for 5 hours to obtain the periclase-magnesia-alumina spinel refractory material for cement rotary kiln.
[0138] Example 9: A periclase-magnesia-alumina spinel refractory material for cement rotary kiln
[0139] 1. Raw materials:
[0140] 25 kg of fused magnesia powder (particle size less than 0.1 mm), 15 kg of active spinel powder (particle size less than 0.1 mm), 1 kg of magnesium-based lanthanum hexaaluminate precursor (prepared in Example 1), 15 kg of fused magnesia aggregate with a particle size of 3-5 mm, 30 kg of fused magnesia aggregate with a particle size of 1-3 mm, 15 kg of fused magnesia aggregate with a particle size of 0.088-1 mm, and 5 kg of polyvinyl alcohol aqueous solution (concentration of 10%).
[0141] Anhydrous ethanol was also used as solvent in the preparation process.
[0142] 2. The preparation steps are:
[0143] Step 1: crush the precursor, pass it through a 0.1 mm sieve to obtain precursor powder, weigh each component according to the raw material, and set aside;
[0144] Step 2: fused magnesia powder, active spinel powder and magnesium-based lanthanum hexaaluminate precursor powder (prepared in Example 1) are wet mixed for 6 hours with anhydrous ethanol as solvent, then dried at 110° C. for 24 hours, and ground to a particle size of less than 0.1 mm to obtain a mixed powder;
[0145] Step 3, placing the fused magnesia aggregate with a particle size of 3-5mm, the fused magnesia aggregate with a particle size of 1-3mm, the fused magnesia aggregate with a particle size of 0.088-1mm and the mixed powder in step 2 in a mixing mill and mixing for 30 minutes to obtain a mixed refractory mud;
[0146] Step 4: Mix the mixed refractory mud and the polyvinyl alcohol aqueous solution, place the mixture in a mold, seal it, and move it to the pressure cabin of the isostatic press. First, increase the pressure to 50MPa at a rate of 4MPa / s, increase the pressure to 80MPa at a rate of 5MPa / s, increase the pressure to 110MPa at a rate of 10MPa / s, increase the pressure to 140MPa at a rate of 6MPa / s, and increase the pressure to 200MPa at a rate of 8MPa / s, and maintain the pressure for 5min; then reduce the pressure to 140MPa at a rate of 5MPa / s, reduce the pressure to 110MPa at a rate of 6MPa / s, reduce the pressure to 80MPa at a rate of 8MPa / s, reduce the pressure to 50MPa at a rate of 5MPa / s, and reduce the pressure to 2MPa at a rate of 5MPa / s; finally unload it to normal pressure; perform cold isostatic pressing to obtain a refractory embryo;
[0147] Step 5: Dry the refractory body at 110° C. for 24 hours, and calcine at 1600° C. for 3 hours to obtain the periclase-magnesia-alumina spinel refractory for cement rotary kiln.
[0148] Example 10: A periclase-magnesia-alumina spinel refractory material for cement rotary kiln
[0149] 1. Raw materials:
[0150] 25 kg of fused magnesia powder (particle size less than 0.1 mm), 15 kg of active spinel powder (particle size less than 0.1 mm), 1 kg of magnesium-based lanthanum hexaaluminate precursor (prepared in Example 3), 15 kg of fused magnesia aggregate with a particle size of 3-5 mm, 30 kg of fused magnesia aggregate with a particle size of 1-3 mm, 15 kg of fused magnesia aggregate with a particle size of 0.088-1 mm, and 5 kg of polyvinyl alcohol aqueous solution (concentration of 10%).
[0151] Anhydrous ethanol was also used as solvent in the preparation process.
[0152] 2. The preparation steps are:
[0153] Step 1: crush the precursor, pass it through a 0.1 mm sieve to obtain precursor powder, weigh each component according to the raw material, and set aside;
[0154] Step 2: fused magnesia powder, active spinel powder and magnesium-based lanthanum hexaaluminate precursor powder (prepared in Example 3) are wet mixed for 6 hours with anhydrous ethanol as solvent, then dried at 110° C. for 24 hours, and ground to a particle size of less than 0.1 mm to obtain a mixed powder;
[0155] Step 3, placing the fused magnesia aggregate with a particle size of 3-5mm, the fused magnesia aggregate with a particle size of 1-3mm, the fused magnesia aggregate with a particle size of 0.088-1mm and the mixed powder in step 2 in a mixing mill and mixing for 30 minutes to obtain a mixed refractory mud;
[0156] Step 4: Mix the mixed refractory mud and the polyvinyl alcohol aqueous solution, place the mixture in a mold, seal it, and move it to the pressure cabin of the isostatic press. First, increase the pressure to 50MPa at a rate of 4MPa / s, increase the pressure to 80MPa at a rate of 5MPa / s, increase the pressure to 110MPa at a rate of 10MPa / s, increase the pressure to 140MPa at a rate of 6MPa / s, and increase the pressure to 200MPa at a rate of 8MPa / s, and maintain the pressure for 5min; then reduce the pressure to 140MPa at a rate of 5MPa / s, reduce the pressure to 110MPa at a rate of 6MPa / s, reduce the pressure to 80MPa at a rate of 8MPa / s, reduce the pressure to 50MPa at a rate of 5MPa / s, and reduce the pressure to 2MPa at a rate of 5MPa / s; finally unload it to normal pressure; perform cold isostatic pressing to obtain a refractory embryo;
[0157] Step 5: Dry the refractory body at 110° C. for 24 hours, and calcine at 1600° C. for 3 hours to obtain the periclase-magnesia-alumina spinel refractory for cement rotary kiln.
[0158] Comparative Example 3: A periclase-magnesia-alumina spinel refractory material
[0159] 1. The raw materials are the same as those in Example 4, except that the magnesium-based lanthanum hexaaluminate precursor is not added.
[0160] 2. The preparation steps are:
[0161] Step 1: Using anhydrous ethanol as solvent, wet-mix the fused magnesia powder and the active spinel powder for 6 hours, and then dry them at 110° C. for 24 hours, and grind them to a particle size of less than 0.1 mm to obtain a mixed powder;
[0162] Step 2, placing the fused magnesia aggregate with a particle size of 3-5mm, the fused magnesia aggregate with a particle size of 1-3mm, the fused magnesia aggregate with a particle size of 0.088-1mm and the mixed powder in a mixing mill and mixing for 30 minutes to obtain a refractory mud after mixing and grinding;
[0163] Step 3, mix the mixed refractory mud and the polyvinyl alcohol aqueous solution, place the mixture in a mold, seal it, move it to the pressure cabin of the isostatic press, first increase the pressure to 50MPa at a rate of 4MPa / s, increase the pressure to 80MPa at a rate of 5MPa / s, increase the pressure to 110MPa at a rate of 10MPa / s, increase the pressure to 140MPa at a rate of 6MPa / s, increase the pressure to 200MPa at a rate of 8MPa / s, and maintain the pressure for 5min; then reduce the pressure to 140MPa at a rate of 5MPa / s, reduce the pressure to 110MPa at a rate of 6MPa / s, reduce the pressure to 80MPa at a rate of 8MPa / s, reduce the pressure to 50MPa at a rate of 5MPa / s, and reduce the pressure to 2MPa at a rate of 5MPa / s; finally unload it to normal pressure; perform cold isostatic pressing to obtain a refractory embryo;
[0164] Step 5: Dry the refractory body at 110° C. for 24 hours, and calcine at 1600° C. for 3 hours to obtain the periclase-magnesia-alumina spinel refractory for cement rotary kiln.
[0165] Comparative Example 4: A periclase-magnesia-alumina spinel refractory material
[0166] 1. The raw materials are the same as those in Example 4, except that fused spinel powder is used instead of active spinel powder, and the particle size of the fused spinel powder is less than 0.1 mm; the chemical composition is: MgO = 34.5-36.5wt%, Al2O3 = 63.5-65.5wt%, CaO ≤ 0.7wt%, SiO2 ≤ 0.9wt%, Fe2O3 ≤ 0.5wt%.
[0167] 2. The preparation steps are:
[0168] Step 1: Weigh each ingredient according to the raw materials and set aside;
[0169] Step 2: Using anhydrous ethanol as solvent, wet-mix the fused magnesia powder, fused spinel powder and precursor powder for 6 hours, and then dry them at 110° C. for 24 hours, and grind them to a particle size of less than 0.1 mm to obtain a mixed powder;
[0170] Step 3, placing the fused magnesia aggregate with a particle size of 3-5mm, the fused magnesia aggregate with a particle size of 1-3mm, the fused magnesia aggregate with a particle size of 0.088-1mm and the mixed powder in step 2 in a mixing mill and mixing for 30 minutes to obtain a mixed refractory mud;
[0171] Step 4: Mix the mixed refractory mud and the polyvinyl alcohol aqueous solution, place the mixture in a mold, seal it, and move it to the pressure cabin of the isostatic press. First, increase the pressure to 50MPa at a rate of 4MPa / s, increase the pressure to 80MPa at a rate of 5MPa / s, increase the pressure to 110MPa at a rate of 10MPa / s, increase the pressure to 140MPa at a rate of 6MPa / s, and increase the pressure to 200MPa at a rate of 8MPa / s, and maintain the pressure for 5min; then reduce the pressure to 140MPa at a rate of 5MPa / s, reduce the pressure to 110MPa at a rate of 6MPa / s, reduce the pressure to 80MPa at a rate of 8MPa / s, reduce the pressure to 50MPa at a rate of 5MPa / s, and reduce the pressure to 2MPa at a rate of 5MPa / s; finally unload it to normal pressure; perform cold isostatic pressing to obtain a refractory embryo;
[0172] Step 5: Dry the refractory body at 110° C. for 24 hours, and calcine at 1600° C. for 3 hours to obtain the periclase-magnesia-alumina spinel refractory for cement rotary kiln.
[0173] Comparative Example 5: A periclase-magnesia-alumina spinel refractory material
[0174] 1. The raw materials are the same as those in Example 4, except that cold isostatic pressing is not used.
[0175] 2. The preparation steps are:
[0176] Step 1: crush the precursor, pass it through a 0.1 mm sieve to obtain precursor powder, weigh each component according to the raw material, and set aside;
[0177] Step 2: The fused magnesia powder 25, the active spinel powder and the magnesium-based lanthanum hexaaluminate precursor powder are wet mixed for 6 hours with anhydrous ethanol as a solvent, and then dried at 110° C. for 24 hours, and ground to a particle size of less than 0.1 mm to obtain a mixed powder;
[0178] Step 3, placing the fused magnesia aggregate with a particle size of 3-5mm, the fused magnesia aggregate with a particle size of 1-3mm, the fused magnesia aggregate with a particle size of 0.088-1mm and the mixed powder in step 2 in a mixing mill and mixing for 30 minutes to obtain a mixed refractory mud;
[0179] Step 4: Mix the mixed and ground refractory material with the polyvinyl alcohol aqueous solution, and perform conventional molding of the mixture at 150 MPa to obtain a refractory body;
[0180] Step 5: Dry the refractory body at 110° C. for 24 hours, and calcine at 1600° C. for 3 hours to obtain the periclase-magnesia-alumina spinel refractory for cement rotary kiln.
[0181] Experimental Example 2: Testing of compressive strength and thermal shock stability
[0182] 1. Samples: Examples 4-10 and Comparative Examples 3-5.
[0183] 2. Detection method:
[0184] 2.1 Compressive strength: room temperature compressive strength test in GB / T 5072-2023 (compressive strength test method for dense shaped refractory products without liner);
[0185] 2.2 Flexural strength retention rate: Method 3 of GB / T 30873-2014, air rapid cooling method, heated to 1100℃ for testing;
[0186] 3. Test results: see Table 1
[0187] Table 1: Compressive strength of various embodiments and comparative examples
[0188]
[0189] The results in Table 1 show that the compressive strength of Examples 4-10 is 85-110 MPa, and the residual flexural strength retention rate after 1100°C thermal shock 3 times and air cooling is not less than 75%. Comparative Example 3 (no magnesium-based lanthanum hexaaluminate precursor powder is added), Comparative Example 4 (partial raw materials are different), and Comparative Example 5 (preparation without cold isostatic pressing) have low compressive strength and flexural strength retention rates.
[0190] The results show that the compressive strength of conventional refractory materials is 40-60MPa and the thermal shock stability is about 40-50% of the residual flexural strength retention rate after 3 air cooling at 1100℃ thermal shock. The material and preparation method provided by the present invention can increase the compressive strength and flexural strength retention rate of refractory materials.
[0191] Experimental Example 3: Testing of resistance to alkaline medium corrosion
[0192] 1. Samples: Example 4 and Comparative Example 3.
[0193] 2. Alkaline medium corrosion test: The static crucible method was used to conduct the alkali corrosion test. Samples with a size of 80 mm × 80 mm × 80 mm were cut from each sample brick, and a cylindrical groove of φ36 mm × 40 mm was drilled in the center to make a crucible. 20 g of commercially available chemically pure K2CO3 was placed in each crucible. The entire crucible was dried in an oven at 110°C for 12 h, then placed in an electric furnace and kept at 1100°C for 3 h, and then cooled naturally. The alkali corrosion resistance of the sample was evaluated by observing the appearance of the sample.
[0194] 3. Results Figure 2 : Appearance of the longitudinal section of the sample after being eroded by alkaline media:
[0195] As can be seen from the figure,
[0196] The permeation boundary of the sample of Example 4 is relatively clear, and the alkaline medium has no obvious permeation along the pore cracks. The periclase-spinel refractory material introduced with magnesium-based lanthanum hexaaluminate has high strength, and the magnesium-based lanthanum hexaaluminate phase has good corrosion resistance, and the alkaline medium is difficult to penetrate, so the corrosion resistance is significantly improved.
[0197] Comparative Example 3: The periclase-spinel refractory material without magnesium-based lanthanum hexaaluminate has an uneven anti-erosion boundary, loose matrix bonding, low strength, and is more likely to cause structural peeling of the material. It is difficult to resist the penetration of alkaline media, and the penetration erosion phenomenon is obvious, such as Figure 2 The location of the black area is marked.
[0198] The results show that the corrosion resistance of conventional refractory materials is similar to that of comparative example 3, and the penetration of the black part is very obvious. The material and preparation method provided by the present invention can effectively improve the ability of refractory materials to resist corrosion by alkaline media.
[0199] In summary, the periclase-magnesium-aluminum-spinel refractory material for cement rotary kiln provided by the present invention has been tested: the compressive strength is 85-110MPa; the residual flexural strength retention rate is not less than 75% after 1100°C thermal shock 3 times and air cooling; and no obvious erosion and penetration are found in the alkaline medium erosion resistance test.
[0200] Therefore, this specific implementation method has low equipment requirements and simple process, and the prepared periclase-magnesium-aluminum spinel refractory material for cement rotary kiln has the advantages of high strength, good thermal shock stability and strong resistance to alkaline medium corrosion.
Claims
1. A periclase-magnesia-alumina spinel refractory material for cement rotary kiln, wherein the raw materials are composed of the following materials in parts by weight: 60 parts aggregate, 30-50 parts powder, 1-5 parts precursor and 5-10 parts binder, The precursor raw material is composed of the following materials in the following amounts: 1 part of magnesium nitrate hexahydrate, 1 part of lanthanum nitrate hexahydrate, 11 parts of aluminum nitrate nonahydrate, and 14 parts of citric acid monohydrate, and is prepared by the following method: weighing each material according to the ratio, mixing, grinding at room temperature for 60 minutes, drying at 110° C. for 12 hours, and then heat treating at 1000° C. for 3 hours to obtain a precursor; The 60 parts of aggregate are composed of the following materials in parts by weight: 10-20 parts of fused magnesia aggregate with a particle size of 3-5mm, 20-40 parts of fused magnesia aggregate with a particle size of 1-3mm, and 10-20 parts of fused magnesia aggregate with a particle size of 0.088-1mm; The 30-50 parts of powder are composed of the following materials in parts by weight: 20-30 parts of fused magnesia powder and 10-20 parts of active spinel powder; The particle size of the fused magnesia powder is less than 0.1 mm; the chemical composition of the fused magnesia powder is: MgO=96.5-97.5wt%, Al2O3≤0.3wt%, CaO≤0.7wt%, SiO2≤0.9wt%, Fe2O3≤0.5wt%; The particle size of the active spinel powder is less than 0.1 mm; the chemical composition of the active spinel powder is: MgO=34.5-36.5wt%, Al2O3=63.5-65.5wt%, CaO≤0.7wt%, SiO2≤0.9wt%, Fe2O3≤0.5wt%; The adhesive is a polyvinyl alcohol aqueous solution with a concentration of 10%.
2. The refractory material according to claim 1, characterized in that The raw materials of the refractory material contain the following materials in parts by weight: 60 parts of aggregate, 35-45 parts of powder, 3-4 parts of the precursor according to claim 1 and 5-10 parts of binder.
3. The refractory material according to claim 1, characterized in that: The 60 parts of aggregate are composed of the following materials in parts by weight: 12-18 parts of fused magnesia aggregate with a particle size of 3-5 mm, 25-35 parts of fused magnesia aggregate with a particle size of 1-3 mm, and 12-18 parts of fused magnesia aggregate with a particle size of 0.088-1 mm.
4. The refractory material according to claim 1, characterized in that: The 60 parts of aggregate are composed of the following materials in parts by weight: 15 parts of fused magnesia aggregate with a particle size of 3-5 mm, 30 parts of fused magnesia aggregate with a particle size of 1-3 mm, and 15 parts of fused magnesia aggregate with a particle size of 0.088-1 mm.
5. The refractory material according to claim 1, characterized in that: The 30-50 parts of powder are composed of the following materials in parts by weight: 25 parts of fused magnesia powder and 12-18 parts of active spinel powder.
6. The refractory material according to claim 1, characterized in that: The particle size of the precursor is less than 0.1 mm, and the precursor needs to be crushed and passed through a 0.1 mm sieve; The purity of the magnesium nitrate hexahydrate is ≥99.9%; the particle size of the magnesium nitrate hexahydrate is ≤5 μm; The purity of the lanthanum nitrate hexahydrate is ≥99.9%; the particle size of the lanthanum nitrate hexahydrate is ≤5 μm; The purity of the aluminum nitrate nonahydrate is ≥99.9%; the particle size of the aluminum nitrate nonahydrate is ≤5 μm; The purity of the citric acid monohydrate is ≥99.9%; the particle size of the citric acid monohydrate is ≤5 μm; The chemical composition of the fused magnesia aggregate is: MgO=96.5-97.5wt%, Al2O3≤0.3wt%, CaO≤0.7wt%, SiO2≤0.9wt%, Fe2O3≤0.5wt%.
7. A method for preparing a refractory material according to claim 1, characterized in that: The method comprises the following steps: Step 1: Weigh each ingredient according to the ratio and set aside; Step 2: Using anhydrous ethanol as solvent, wet-mix the fused magnesia powder, active spinel powder and precursor powder for 3-8 hours, and then dry at 90-130° C. for 12-36 hours, and grind to a particle size of less than 0.1 mm to obtain a mixed powder; Step 3, placing the fused magnesia aggregate with a particle size of 3-5mm, the fused magnesia aggregate with a particle size of 1-3mm, the fused magnesia aggregate with a particle size of 0.088-1mm and the mixed powder in step 2 in a mixing mill and mixing for 30 minutes to obtain a mixed refractory mud; Step 4: Mix the refractory material mud and the binder after mixing and grinding in step 3, put the mixture into a mold, seal it, move it to the pressure cabin of the isostatic press, and perform cold isostatic pressing to obtain a refractory embryo body; The specific operation of the cold isostatic pressing is: first, the pressure is increased to 50MPa at a rate of 4MPa / s, increased to 80MPa at a rate of 5MPa / s, increased to 110MPa at a rate of 10MPa / s, increased to 140MPa at a rate of 6MPa / s, increased to 200MPa at a rate of 8MPa / s, and maintained for 5min; then, the pressure is reduced to 140MPa at a rate of 5MPa / s, reduced to 110MPa at a rate of 6MPa / s, reduced to 80MPa at a rate of 8MPa / s, reduced to 50MPa at a rate of 5MPa / s, and reduced to 2MPa at a rate of 5MPa / s; finally, the pressure is unloaded to normal pressure; Step 5: Dry the refractory material body at 100-120° C. for 12-36 hours, and calcine at 1600-1800° C. for 3-5 hours to obtain the periclase-magnesia-alumina spinel refractory material for cement rotary kiln.
Citation Information
Patent Citations
Magnesia-alumina spinel skinning-resistant non-amorphous refractory material for cement kiln as well as preparation method and application thereof
CN102391002A
Periclase-calcium-containing spinel brick for cement rotary kiln burning zone and preparation method thereof
CN103467121A
Lightweight periclase-magnesium aluminate spinel refractory material for rotary cement kiln and preparation method thereof
CN103864434A
Chromium-free fireproof material used for cement rotary kiln and having excellent kiln coating adhering performance
CN105314992A
Method for preparing magnesium-based lanthanum hexaaluminate powder through co-ion complexing
CN106518046A